Improving the Quality of Children's Faith Formation through Catechesis for First Communion Preparation in the Parish with a Holistic Approach - Tarihoran, Emmeria; Firmanto, Antonius Denny; Kurniawan, Alponsus Zeno (Badan Litbang dan Diklat Kementerian Agama RI, 2024)
This study aims to evaluate and improve the quality of children's faith formation through catechesis preparation for First Communion in the Parish. The research method is descriptive quantitative, with data collected using surveys through Google Forms. The study population consists of parents or guardians of children preparing for First Communion, with a sample of 23 respondents. Data analysis uses descriptive statistics. The findings indicate that catechesis activities and children's experiences preparing for First Communion significantly impact the quality of children's faith formation. Most respondents reported positive experiences and perceived improvements in their children's understanding and practice of the Catholic faith. However, factors inhibiting optimal faith formation were also identified, particularly the need for increased parental involvement. The study recommends encouraging parental participation, providing necessary resources and guidance for active engagement in children's religious education. To enhance children's faith formation, collaboration between parents, churches, and catechists is recommended, along with establishing effective communication channels between these stakeholders.